(untitled) (The Pakistan Development Review, 2009)
Pakistan’s education system has been the focus of various reforms every few years, and a new exercise has been initiated recently through the National Education Policy, 2009. While the problems are generally well documented and stress on universal primary education fully justified, the role of economic relevance of education and training as a factor discouraging completion is not sufficiently emphasised. Studies from developing and developed countries highlight the strong linkage between education and training and employment, and the economic and social returns of employability of trained workers. It is argued that if one or more career based occupational tracks (vocationalisation of upper-secondary education) is offered at the upper secondary level (Class 8-10) as supplements to general education, dropout can be reduced. This will result in increased employability, productivity and competitiveness in the work environment. Co-financing with the private sector of a Rs 48 billion programme for practical on-the-job training is examined in the light of international experiences. JEL classification: J24, O33, H52 Keywords: Human Capital, Skill Bias, Labour Productivity, Education Expenditures